The Analysis of Hadith Prohibition of Building Above Graves Perspective of the Community of Kampung Mahmud Bandung Selatan: Analisis Hadis Larangan Mendirikan Bangunan di atas Kuburan Perspektif Masyarakat Kampung Mahmud Bandung Selatan - Asty Oktaviani; Hartati, Hartati; Hasyim, Ahmad Faqih (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2023)
The Prophet forbade his ummah not to build buildings over graves because they did not want to be like the previous people, namely the ummah of Noah as who worshiped their ancestors and the ignorant Arab people who worshiped idols. However, this prohibition is realized by society today with various perspectives. This paper aims to find out the perspective of the Kampung Mahmud Community towards the hadith prohibiting building over graves through two basic questions; first, how is the concept of graves and the prohibition of building over graves in Islam?, and second, how is the understanding of the people of Kampung Mahmud in understanding the prohibition of building over graves?.. The method used is a qualitative-descriptive method by collecting all observational data, interviews and documentation were then analyzed using the sociology of knowledge approach developed by Begger and Luckmann, namely social construction theory which includes three aspects, externalization, objectivation and internalization. The results of this study indicate that the Mahmud village community allows building over graves with several conditions that have been mutually agreed upon, namely that it must be built on private land and the center of the grave must be empty. They also forbid the construction of buildings over graves if they are used for worship.